2003
DOI: 10.1002/cncr.11771
|View full text |Cite
|
Sign up to set email alerts
|

Intraarterial cisplatin with intravenous paclitaxel and ifosfamide as an organ‐preservation approach in patients with paranasal sinus carcinoma

Abstract: A cobalt‐catalyzed reductive coupling of terminal alkynes, RCCH, with activated alkenes, R′CHCH2, in the presence of zinc and water to give functionalized trans‐disubstituted alkenes, RCHCHCH2CH2R′, is described. A variety of aromatic terminal alkynes underwent reductive coupling with activated alkenes including enones, acrylates, acrylonitrile, and vinyl sulfones in the presence of a CoCl2/P(OMe)3/Zn catalyst system to afford 1,2‐trans‐disubstituted alkenes with high regio‐ and stereoselectivity. Similarly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 32 publications
(37 reference statements)
0
29
0
Order By: Relevance
“…Only two patients underwent the surgical removal of an eye due to tumour recurrence at the primary site, and only one patient experienced optic nerve dysfunction and mild brain damage; the visual acuity of the other patients did not decrease. The Padimitrakopoulou study (6) reported an EOP of 88% immediately after treatment involving orbital organ preservation for 24 cases of patients with locally advanced paranasal sinus carcinoma; however, long-term follow-up revealed 1 case of optic atrophy, 1 case of cataract and 1 case of corneal disease complicated with iritis, reducing the EOP to 78%. Regarding other side effects, thanks to the application of ICT followed by CCRT and/or EGFR molecular targeted therapy and the use of high-precision HT, common vision-related side effects (including dry eye syndrome, conjunctivitis and keratitis) were controlled at Grade 2 or lower in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only two patients underwent the surgical removal of an eye due to tumour recurrence at the primary site, and only one patient experienced optic nerve dysfunction and mild brain damage; the visual acuity of the other patients did not decrease. The Padimitrakopoulou study (6) reported an EOP of 88% immediately after treatment involving orbital organ preservation for 24 cases of patients with locally advanced paranasal sinus carcinoma; however, long-term follow-up revealed 1 case of optic atrophy, 1 case of cataract and 1 case of corneal disease complicated with iritis, reducing the EOP to 78%. Regarding other side effects, thanks to the application of ICT followed by CCRT and/or EGFR molecular targeted therapy and the use of high-precision HT, common vision-related side effects (including dry eye syndrome, conjunctivitis and keratitis) were controlled at Grade 2 or lower in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Nishimura et al (5) showed that the survival rate of patients who received radiotherapy after induction chemotherapy (ICT) for orbital organ preservation was not significantly affected compared with those who received postoperative radiotherapy. Papadimitrakopoulou et al (6) reported the application of a non-surgical multimodal treatment for orbital organ preservation in 24 cases of patients with paranasal sinus tumours, among whom the 2-year overall survival rate (OS) was 60% and the effective orbital preservation rate (EOP) was 88%. Therefore, the current guidelines published by the international authority on cancer, the National Comprehensive Cancer Network (NCCN), recommend chemoradiotherapy or clinical trials for patients with orbital involvement of T4b SCCNP based on American Joint Committee on Cancer (AJCC) staging.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have evaluated this approach with conflicting results in terms of outcome and toxicities [34,35]. The late toxicities reported in some experiences, including osteonecrosis, brain necrosis and ocular and visual problems, question the impact of this strategy on global quality of life of the patients [36,37].…”
Section: Intra-arterial Approachesmentioning
confidence: 97%
“…23 Papadimitrakopoulou et al reported that a cerebrovascular accident occurred in 10% of patients. 25 Foote et al reported transient left hemiplegia in 5.26% of patients. 26 This risk is lower when retrograde catheterization is performed from the peripheral side.…”
Section: Discussionmentioning
confidence: 98%